THE FROMMELT ATTITUDES TOWARD CARE OF THE DYING CARE FORM B (FATCOD-B) INDONESIA VERSION: MEASUREMENT VALIDITY USING FACTOR ANALYSIS IN NURSING STUDENTS - Muhamad Zulfatul A'la (NurseLine Journal, 2016)
Analysis of nursing students' attitudes towards caring for the dying patient needs to beexplored. The Frommelt Attitudes Toward Care of the Dying Care Form B (FATCOD-B) has not previously been adopted and used in the Indonesian language. The aim of this study was to determine the reliability, validity and factor analysis of FATCOD-B Indonesian version (FATCOD-B-I). A descriptive and cross-sectional was used. Reliability test was using Cronbach's alpha coefficient, the validity was using the Pearson correlation and confirmatory factor analysis (CFA). Factor analysis of FATCOD-B-I was in accordance with FATCOD-B Swedish version with two factors, the factor 1 (positive attitude toward caring for the dying patient) and factor 2 (perception of patient-and familycentered care). The sample consisted of 127 nursing students in Universitas Jember. Reliability test was 0.680. It was higher than in the FATCOD-B Swedish version and lower than FATCOD Chinese version. Pearson correlation in all items of FATCOD-B-I was valid with a range 0,544 -0.278. Bartlett test value was p = 0.00 and the value of test Kaiser-Meyer-Olkin (KMO) was 0.639. So it could be used CFA. there were the 4 item differences in factor I, it was item of 15, 11, 5, 7 and 14. There were 8 items differences in Factor 2, it was item of 2, 25, 20, 21, 18, 12, 27 and 22 with FATCOD-B Swedish version. The FATCOD-B-I have enough reliability value and all items of FATCOD B-I have valid statement. The results of the confirmatory factor analysis CFA was a difference with FATCOD Swedish version. For further research, it needed for psychometric test in FATCOD-B-I widely and it was including more diverse cultural aspects in Indonesia.